Theoretical and legal problems of the nature of the collective agreement as a local regulation - Тищенко, Олена Володимирівна; Артюх, Юлія Ігорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article investigates the theoretical and legal problems of the nature of the collective agreement as anact of local rule-making. Analyzes trends in labor law, which governs collective bargaining, examines the prospects for its reform.